Goat medicine - Smith, Mary C. (Blackwell Pub., 2007)
This book can help the owner/manager recognize symptons, understand prevention and work out reasonable treatments...treatments that work into an already too busy day. Yes, there is theory.... Great if you like to understand and run ideas through your own head. skip that part, if it doesn't make sense, and go onto more basics-- prevention, control, treatment.